A estética do erro digital - Fernandes, José Carlos Silvestre (2010)
This dissertation proposes an outline of an aesthetics of the error in Digital Art. We start with a survey of works in Digital Art that explore the theme of the error, and advance a rigorous definition of what we call error, to introduce our main hypothesis: that the error is a revealing of the Materiality of Informatics. We investigate the particularities of this materiality and this revealing, fundamented in authors such as Hayles, Kittler, Simondon and Fuller. Next, we consider the cultural reverberations of the error state from this revealing of materiality: its subversive connotations, its association with hacker culture, and its sub-text of nostalgia. Our main sources for this second part are Kittler, Stiegler and Pias. Throughout our theoretical discussion, we analyse the works of many artists to demonstrate how each of these themes and concerns are explored therein; we give particular attention to the works of Ant Scott, JODI, and Cory Arcangel. We adopt, however, an anti-hermeneutic approach to most works, molded after the practice of Friedrich Kittler: an emphasis in the technical and social systems implicated rather than in interpretation and a search for meaning contained in the works themselves. We hope to finally present a theoretical framework which may support the analysis and exploration of the aesthetics of error, a fairly unprecedented topic. Moreover, much of our discussion is of interest in fields beyond Digital Art